MODIFICATION OF LOAD BALANCING METHOD IN NETWORKS WITH WIMAX TECHNOLOGY - Amin Salih Mohammed; Ahmed, Farah Qasim Ahmed; Bnar Fareed Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The main consideration of Mobile WiMAX is to achieve seamless handover such that there is no loss of data. In WiMAX both mobile station (MS) and a base station (BS) scans the neighboring base stations for selecting the best base station for a potential handover. This paper presents an analysis of the particularities of handover process in modern wireless and mobile networks, as well as the factors that impact such process. Several factors affect the quality of mobile networks functioning, one of them is the process of handover. Moreover, a method that allows mobile hosts with equal or close signal-noise ratio to switch to the less loaded base station is proposed; which allows such base station to initiate handover process to distribute all the loadings from mobile hosts more uniformly between the nearest base stations. The method gives accurate and timely decisions and considerably decreases of data transfer time using all